PENGARUH PENGGUNAAN AGREGAT DAUR ULANG TERHADAP KUAT TEKAN DAN MODULUS ELASTISITAS BETON BERKINERJA TINGGI GRADE 80 - Anwar Hamid, Deni; As'ad, Solihin; Safitri, Endah (Program Studi Teknik Sipil FT UNS, 2014)
There are abundant concrete waste taken from new buildings construction and demolished the old one. Most of them are not reused and dumped.This material can be recycled into new concrete aggregate by recycling waste concrete. This study aims to know the effect of the use of recycled fineaggregate as natural aggregates replacement on the compressive strength and modulus of elasticity on the high performance concrete grade 80 orminimum 80 MPa. The portion of recycled fine aggregate used was 0%, 20%, 40%, 60%, 80% and 100% of the total weight of natural fineaggregate. Specimens used were concrete cylinders form with a diameter of 7.62 cm and 15.24 cm of height. The reference concrete compressivestrength was fc '= 80 MPa. From the test results obtained that the compressive strength of reference concrete was 85.51 MPa or compatible withthe strength target. Replacement of natural fine aggregate with 20% recycled decreased the compressive strength significantly. This equals to20.97% (from 85.51 MPa to 67.58 MPa). The strength reduction then continued the next replacement 40% (fc '= 62.06 MPa), 60% (fc' =60.68 MPa), 80% (fc '= 57.92 MPa), 100% (fc' = 53.79 MPa). Modulus of elasticity of concrete also decreases following compressive strengthdrop. This equals was 0% (Ec=49,045 GPa), 20% (Ec=41,827 GPa), 40% (Ec=38,127 GPa), 60% (Ec=34,689 GPa), 80%(Ec=30,008 GPa), 100% (Ec=27,739 GPa).